THU0429 Nailfold video capillaroscopy and deterioration of skin involvement and lung function tests in systemic sclerosis: a 3-year prospective study. (12th June 2018) - Bournia, V.-K.; Kottas, K.; Iliopoulos, A.; Sfikakis, P.P.; Vlachoyiannopoulos, P.
Abstract : Background: Nailfold video-capillaroscopy(NVC) is a non-invasive method to assess peripheral microangiopathy. Abnormal capillaroscopic patterns are almost universally found in patients with Systemic Sclerosis (SSc) and assist the diagnosis of SSc. However, little is known about the prognostic value of NVC in skin and lung involvement progression in these patients. Objectives: To test the hypothesis that baseline capillaroscopic indices, as well as possible changes in capillaroscopic indices over time, correlate with deterioration in skin thickening and lung function tests in a prospective SSc cohort. Methods: Fifty-five consecutive SSc patients from a tertiary care university centre (49 women, 29 limited cutaneous SSc, mean age: 50.84±14.88 years, mean disease duration 6.74±6.25 years) were evaluated by NVC at baseline and after a median of 3.1 years. Qualitative assessment of NVC findings permitted categorization of patients to a predominantly normal, early, active or late capillaroscopic pattern. Capillary loss, capillary dilatation, giant or ramified capillaries and microhemorrhages were further assessed using a semi-quantitative rating scale (score 0–3), derived as the mean of three fields in each of the 2nd, 3rd, 4th and 5th finger of both hands. Scoring was performed by two different assessors. Skin thickening was measured using the modified Rodnan Skin Score (mRSS). FVC and DLCO were performed within 6 months from the NVC. Deterioration in FVC and DLCO was considered clinically significant when>10%. Between baseline and follow-up evaluation 36% of patients had been receiving both major antiproliferative and vasodilator therapy, while15% and 29% had been receiving only antiproliferative or vasodilator therapy, respectively. Results: Intraclass correlation coefficient (ICC) for interrater reliability analyses was very good for all semi-quantitative capillaroscopy scores [ICC: 0.97 (0.74–0.99) for capillary loss score, 0.94 (0.85–0.98) for dilatation score, 0.98 (0.97–0.99) for giant score, 0.94 (0.84–0.97) for microhemorrhages score), except for the ramification score [ICC: 0.52 (-0.2, –0.81)] which was excluded from all analyses. Linear regression, adjusted for age and gender, showed no association between either baseline capillaroscopy scores or of their changes and changes in mRSS over time. FVC and DLCO deteriorated in 13 and 11 patients, respectively. Binary logistic regression analysis adjusted for age and gender showed no association either baseline capillaroscopy scores or of their changes with deterioration in FVC or DLCO, with the exception of the change in microhemorrhages score, which correlated inversely with deterioration in FVC [p=0.013, Odds Ratio=0.051 (CI: 0.005–0.534)]. Regarding qualitative analysis of capillaroscopic findings, the baseline capillaroscopy pattern remained unchanged in 35, deteriorated in 15 and improved in 5 patients. No difference was found between these 3 groups regarding change in mRSS (ANOVA, p=0.634), deterioration in FVC (x 2 test, p=0.502) or deterioration in DLCO (x 2 test, p=1.00). Conclusions: Although a possible confounding effect of treatment cannot be excluded, NVC seems to have poor prognostic value for the progression of skin thickening and interstitial lung disease in rigorously treated SSc patients. Disclosure of Interest: None declared